Bio-oils from pyrolysis of oil palm empty fruit bunches - Sukiran, M.A.; Chin, C.M.; Bakar, N.K.A. (2009)
The palm oil industry generates an abundance of oil palm biomass such as the mesocarp fibre, shell, empty fruit bunch (EFB), frond, trunk and palm oil mill effluent (POME). For 80 million tonnes of fresh fruit bunch (FFB) processed last year, the amount of oil palm biomass was more than 25 million tones. The objectives of this study were to: (i) Determine the effect of various pyrolysis parameters on product yields and (ii) Characterise liquid product obtained under different condition. Approach: In this study, pyrolysis of oil palm Empty Fruit Bunches (EFB) was investigated using quartz fluidized fixed bed reactor. The effects of pyrolysis temperatures, particle sizes and heating rates on the yield of the products were investigated. The temperature of pyrolysis and heating rate were varied in the range 300-700 °C and 10-100 °C min1 respectively. The particle size was varied in the range of <90, 91-106, 107-125 and 126-250 μm. The elemental analysis and calorific value of the bio-oil were determined. The chemical composition of the oil was investigated using chromatographic and spectroscopic techniques. Results: Under the experimental conditions, the maximum bio-oil yield was 42.28 obtained at 500 °C, with a heating rate of 100 °C min-1 and particle size of 91-106 μm. The calorific values of bio-oil ranged from 20-21 MJ kg-1. A great range of functional groups of phenol, alcohols, ketones, aldehydes and carboxylic acids were indicated in FTIR spectrum. Conclusion: The chemical characterisation results showed that the bio-oil obtained from oil palm EFB maybe a potentially valuable source as fuel or chemical feedstocks.